Navigation of Fluorescence Cameras during Soft Tissue Surgery—Is it Possible to Use a Single Navigation Setup for Various Open and Laparoscopic Urological Surgery Applications? - Van Oosterom, Matthias N.; Meershoek, Philippa; Kleinjan, Gijs H.; Hendricksen, Kees; Navab, Nassir; Van De Velde, Cornelis J. H.; Van Der Poel, Henk G.; Van Leeuwen, Fijs W. B. (Journal of Urology, 2018)
Purpose: Real-time visualization fluorescence imaging can guide surgeons during tissue resection. Unfortunately tissue induced signal attenuation limits the value of this technique to superficial applications. By positioning the fluorescence camera via a dedicated navigation setup we reasoned that the technology could be made compatible with deeper lesions, increasing its impact on clinical care. Such an impact would benefit from the ability to implement the navigation technology in different surgical settings. For that reason we evaluated whether a single fluorescence camera could be navigated toward targeted lesions during open and laparoscopic surgery. Materials and Methods: A fluorescence camera with scopes available for open and laparoscopic procedures was integrated with a navigation platform. Lymph nodes identified on SPECT/CT (single photon emission computerized tomography/computerized tomography) or free-hand single photon emission computerized tomography acted as navigation targets and were displayed as augmented overlays in the fluorescence camera video feed. The accuracy of this setup was evaluated in a phantom study of 4 scans per single photon emission computerized tomography imaging modality. This was followed by 4 first in human translations into sentinel lymph node biopsy procedures for penile (open surgery) and prostate (laparoscopic surgery) cancer. Results: Overall the phantom studies revealed a tool-target distance accuracy of 2.1 mm for SPECT/CT and 3.2 mm for freehand single photon emission computerized tomography, and an augmented reality registration accuracy of 1.1 and 2.2 mm, respectively. Subsequently open and laparoscopic navigation efforts were accurate enough to localize the fluorescence signals of the targeted tissues in vivo. Conclusions: The phantom and human studies performed suggested that the single navigation setup is applicable in various open and laparoscopic urological surgery applications. Further evaluation in larger patient groups with a greater variety of malignancies is recommended to strengthen these results.
CRIS-Team Scopus Importer:2023-03-08
Keywords: computer-assisted; emission-computed; laparoscopy; optical imaging; sentinel lymph node; single-photon; surgery; tomography